(untitled) (REMUNOM, 2024)
Type 1 Diabetes Mellitus (T1D) is a chronic metabolic disease that can be characterized by an insulin deficiency, being caused by the destruction of insulin-producing cells in the pancreas. DM1 presents an epidemiological picture that has only been growing in many regions. Insulin deficiency generates high rates of glucose in the blood, harming the health as a whole of those affected by it. The mechanisms that are involved in this destruction of cells are not yet totally clear, but studies indicate that antigens from the lesion of pancreatic cells are recognized by the immune system that in a dysregulated action induces this process of insulitis. It is necessary to determine what are the factors that are related to the beginning of the process of autoimmunity so that a better control and prevention of this disease that affects more and more people in the world can be achieved. This article, based on the perception of the need for knowledge of the immunological mechanisms of the disease and the importance of nursing care in therapeutics, seeks to relate and present the knowledge obtained through research on the subject available in the academic collection of scientific articles, showing that understanding the disease and immunopathogenic mechanisms can be collaborators for the elaboration of new therapeutic perspectives in the treatment and monitoring of diabetic patients.